2020
DOI: 10.1002/ece3.6218
|View full text |Cite
|
Sign up to set email alerts
|

Skin hydrophobicity as an adaptation for self‐cleaning in geckos

Abstract: Hydrophobicity is common in plants and animals, typically caused by high relief microtexture functioning to keep the surface clean. Although the occurrence and physical causes of hydrophobicity are well understood, ecological factors promoting its evolution are unclear. Geckos have highly hydrophobic integuments. We predicted that, because the ground is dirty and filled with pathogens, high hydrophobicity should coevolve with terrestrial microhabitat use. Advancing contact‐angle (ACA) measurements of water dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 98 publications
(170 reference statements)
0
18
0
Order By: Relevance
“…So, the observed negative relationship between contact angle and anole body size in this study is likely a scaling effect, a mere consequence of the microstructure ratio of anoles approaching 10:1 with decreasing body size. Indeed, our statistical models showed that both spinule length and scale size explain a large portion of the variation in contact angle, with longer spinules and smaller scales positively influencing skin surface hydrophobicity; Riedel et al (2020) found the exact same form-function relationship in Australian geckos.…”
Section: Hydrophobic Hierarchically Structured Surfacesmentioning
confidence: 52%
See 3 more Smart Citations
“…So, the observed negative relationship between contact angle and anole body size in this study is likely a scaling effect, a mere consequence of the microstructure ratio of anoles approaching 10:1 with decreasing body size. Indeed, our statistical models showed that both spinule length and scale size explain a large portion of the variation in contact angle, with longer spinules and smaller scales positively influencing skin surface hydrophobicity; Riedel et al (2020) found the exact same form-function relationship in Australian geckos.…”
Section: Hydrophobic Hierarchically Structured Surfacesmentioning
confidence: 52%
“…Earlier functional histological research suggests that a spinulate oberhautchen in the common ancestor of anoles might have played an important role in facilitating ecdysis ( Alibardi and Maderson, 2003 ; Bauer, 2019 ; Irish et al, 1988 ; Maderson, 1970 ). Other hypotheses include functions such as self-cleaning and anti-fouling, reduction of friction and wear protection, as has been shown in geckos ( Riedel et al, 2020 ; Spinner et al, 2013 ; Watson et al, 2015a , b ). To fill this gap, future studies on the functional and ecological significance of spinules should explore the more basal iguanid and gekkotan lineages and focus on species that carry simple spinulate microarchitecture but lack setae and functional toepads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since all anoles we submerged developed a plastron, including many that rarely, if ever, occur near water, the plastron is unlikely to Report be an adaptation for diving. More likely, the anole plastron arose as an evolutionary ''spandrel'' 44 -the byproduct of skin hydrophobicity that evolved for some other purpose (e.g., to shed rainwater or dew, 45 or for anti-fouling via the ''lotus effect'' 46 , as has been shown in geckos [47][48][49] ).…”
Section: Exaptation and The Repeated Evolution Of Specialized Rebreathingmentioning
confidence: 99%